(3JfXje h GOGQI GdOQS aj GdJQHjI GdHOfjI h GdJYde GdMQcjs - (3YHO Gddg YHO GdaJGMs; (3YRg MeOj s ((3GdGScfOQjIs (3GdecJHI GdeUQjIs, 2004)
(3JfXje h EOGQI GdOQhS aj GdJQHjI GdHOfjI hGMOI ef Cge GdTHcGJ GdcHjQI ddJQHjI GdYGeI OGNd GdeOQSI GP JWQb Gdi GdJWhQ GdJGQjNj dWQjbI GdJOQjS ,h QcR Ydi CgejI Cf jchf GdeOQS edeG HLhGfH GdehVhY h Cge h LgGJ GdfXQ GdJj JYQVJ ddOQS(B.s
Keywords: (3GdJQHjI GdHOfjI(B_(3CSGdjH GdJOQjSs